Sequestered plunging ranula: a case report and literature review - Ramji, Ashwath Narayan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Ranula are swellings arising from the sublingual or submandibular salivary glands either due to mucus extravasation or the formation of mucus retention cysts. They are located on the floor of the mouth, generally have an insidious course and remain asymptomatic unless they grow very large or develop secondary complications. Occasionally, by dividing through cervical facial planes, they present as swellings in the neck, aptly called plunging ranulas. Plunging ranulas, therefore, have an intra-oral component and an extra-oral component; however rarely, the intra-oral component resolves leaving behind an isolated swelling in the neck, making the diagnosis a clinical challenge.